Menghargai Masa Lalu: Sosialisasi Sejarah Lokal untuk Membentuk Generasi yang Berintegritas di SMA 2 Majene - Patahuddin, Patahuddin; Subair, Ahmad; Asmunandar, Asmunandar; Amirullah, Amirullah (Humanis, 2024)
Respecting the Past: Socialization of Local History to Form a Generation with Integrity at SMA 2 Majene aims to increase students' understanding and appreciation of local history. The program involves a combination of classroom learning and field activities, including visits to historical sites and dialogue with historians and local residents. To measure the effectiveness of the program, a pre-test and post-test were carried out on 30 students participating in the program. The average pre-test score was 60, while the average post-test score increased significantly to 80.67. An average increase of 20.67 points shows the program's success in increasing students' knowledge and appreciation of local history. This data is supported by qualitative feedback which shows an increase in student enthusiasm and interest in historical material. This program not only enriches students' understanding, but also fosters pride in local cultural heritage. It is hoped that the long-term impact of this program will be to form a young generation that has a high historical awareness and is able to preserve their cultural heritage. The success of this program can be a model for other schools in developing similar programs to strengthen local history education. Abstract. Menghargai Masa Lalu: Sosialisasi Sejarah Lokal untuk Membentuk Generasi yang Berintegritas di SMA 2 Majene bertujuan untuk meningkatkan pemahaman dan apresiasi siswa terhadap sejarah lokal. Program ini melibatkan kombinasi pembelajaran di kelas dan kegiatan lapangan, termasuk kunjungan ke situs-situs bersejarah serta dialog dengan ahli sejarah dan warga setempat. Untuk mengukur efektivitas program, dilakukan pre-test dan post-test terhadap 30 siswa peserta program. Rata-rata nilai pre-test adalah 60, sedangkan rata-rata nilai post-test meningkat signifikan menjadi 80.67. Peningkatan rata-rata sebesar 20.67 poin menunjukkan keberhasilan program dalam meningkatkan pengetahuan dan apresiasi siswa terhadap sejarah lokal. Data ini didukung oleh umpan balik kualitatif yang menunjukkan peningkatan antusiasme dan minat siswa terhadap materi sejarah. Program ini tidak hanya memperkaya pemahaman siswa, tetapi juga menumbuhkan kebanggaan akan warisan budaya lokal. Dampak jangka panjang dari program ini diharapkan dapat membentuk generasi muda yang memiliki kesadaran sejarah yang tinggi dan mampu melestarikan warisan budaya mereka. Keberhasilan program ini dapat menjadi model bagi sekolah lain dalam mengembangkan program serupa untuk memperkuat pendidikan sejarah lokal